The effectiveness of an intervention designed based on health action process approach on diet and medication adherence among patients with type 2 diabetes: a randomized controlled trial - Soheila Ranjbaran; Davoud Shojaeizadeh; Tahereh Dehdari; Mehdi Yaseri; Elham Shakibazadeh (Diabetology & Metabolic Syndrome, 2022)
Abstract Background Diabetes is a major cause of worldwide morbidity and mortality. Diet and medication non-adherence are common among individuals with diabetes, making glycemic control difficult to attain. This study aimed to evaluate an intervention designed based on Health Action Process Approach (HAPA) to improve adherence to diet and medication among patients with type 2 diabetes in Tehran, Iran. Methods The study was a randomized controlled trial. A total of 248 patients with type 2 diabetes who had low diet and medication adherence were randomly allocated into two intervention (n  = 124) and control (n  = 124) groups. Intervention group received educational intervention during three months. HAPA constructs, diet and medication adherence, and Hemoglobin A1c (HbA1c) levels were assessed at baseline, one month and six months after the intervention. Mixed Model Analysis was used to compare between and within group changes in the outcomes. Results There was a statistically significant improvement in HbA1c levels after six months (7.77 ± 1.36% vs. 8.07 ± 1.52%, 95% CI, p  < 0.001). Diet and medication adherence, intention, task self-efficacy, coping self-efficacy, recovery self-efficacy, action and coping planning, barriers, benefits and perceived social support were significantly improved one month and six months after the intervention (p  < 0.001). Conclusion Our intervention designed based on health action process approach led to improvements in diet and medication adherence, and HbA1c among the patients within one and six months. Trial registration: IRCT, IRCT20151208025431N4. Registered 10 March 2018, https://fa.irct.ir